Response of seed enhancement treatments in improving vigour under elevated temperature conditions in Indian mustard - GHANSHAM DAN,; SHIV K. YADAV,; NAVEEN SINGH, (Seed Research, 2026)
Role of seed treatments for enhancement of seed vigour in response to temperature was investigated on two varieties of Indian mustard (Brassica juncea); Pusa Mustard 28 and Pusa Karishma. Both the varieties were given different presowing treatments viz. hydropriming (17h/20°C); halopriming (100µM CaCl, for 18h/20°C); halopriming (0.3% KNO, for 18h/20°C); salicylicacid (1500µM SA for 18 h/ 20°C); osmopriming (20% PEG8000 for 18h/20°C); IncoTec QR (0.02 gm/1000 seed); genius coat 172 (2.5g a.i./kg seed); IncoTec 220 (800 µl/gm gm seed) and thiram (2gm/kg seed) and compared with untreated control. The varieties were subjected to elevated temperatures of 30°C and 35°C, while temperature of 20°C was taken as control. Temperature stress influenced various quality parameters in all treatments. Results revealed that there were significant differences among the varieties for root length, shoot length and vigour index I under temperature stress conditions. The tolerant variety, PM 28 resulted in significantly higher vigour index I and shoot length than susceptible variety, Pusa Karishma. The maximum first count per cent, germination per cent, root length, shoot length, vigour index I and II and minimum percentage of abnormal seedling, hard seeds and dead seeds were observed in salicylic acid, KNO, and hydropriming seed treatments. Salicylic acid had significant effect on all above parameters than KNO, and hydro priming under temperature stress conditions. Therefore, salicylic acid priming and halopriming with KNO, could be used to improve vigour of brassica under temperatures stress conditions.